Maqasid Sharia Index and Efficiency Indonesian Sharia Banking: Pre-Merger & Post Merger - Riyang Mardini; Irena Paramita Pramono; Rudy Hartanto; Fathurahman Marshall Avicenna; Ilmawati Aranni; Rida Adinda (Universitas Islam Bandung, 2022)
This study aims to examine the impact of the merger of PT Bank Syariah in Indonesia Tbk on the level of efficiency and performance of Islamic finance in Islamic banking in Indonesia. The research period used is one year before the merger, and after the merger, in year 2019 and 2021 at Bank Umum Syariah Indonesia. This study uses a quantitative research model that uses secondary data in the form of quarterly financial reports obtained from the annual report. The data analysis used is a non-parametric approach Data Envelopment Analysis (DEA) and Maqasid Syariah Index (MSI) to measure the level of efficiency of the financial performance of the Islamic banking industry in Indonesia through three main categories of Ibn Ashur's maqashid sharia developed by Abu Zahrah, namely tahdzib al-fard ( individual education), iqamah al-adl (justice) and maslahah (welfare). The result of this study show that Islamic Financial Performance and Efficiency Level have not shown a significant increase.